Preoperative remote consultation for a green bariatric surgery: can telemedicine be safe for patients and sustainable for the environment? - Conte, Luigi Eduardo; Orsi, Michela; Peruzzi, Alessandro; Fantozzi, Chiara; Campanelli, Michela; Benavoli, Domenico; Sensi, Bruno; Gentileschi, Paolo (Frontiers in Surgery, 2025)
BackgroundThe increasing emphasis on sustainability and digitalization has brought telemedicine to the forefront, particularly in bariatric surgery. This study evaluates the safety, clinical effectiveness and environmental impact of telemedicine for patients with obesity eligible for bariatric surgery.Materials and methodsA total of 338 patients underwent remote consultations via Zoom in 2023. Median age was 38 years (±4); 70% of patients were female. Mean BMI before surgery was 43 kg/m2 (±5). Surgical procedures included One Anastomosis Gastric Bypass (50%), Sleeve Gastrectomy (20%), Roux-en-Y Gastric Bypass (20%), revisional surgery (8%), and other procedures (2%). CO2 emissions were estimated based on the avoided travel, considering patient-reported transportation methods and distances. All patients were later evaluated in person before hospital admission. The primary outcome was environmental impact; the secondary outcome was whether remote evaluations influenced surgical indication or perioperative management.ResultsRemote consultations reduced total travel emissions from 50,766.01 kg to 17.73 kg CO2, a 99.97% reduction (from 150.20 kg to 0.05 kg per patient). No patients required additional telemedicine or outpatient visits. Surgical indications and preoperative plans remained unchanged after in-person consultations. Postoperative complications occurred in 7.4% of patients, all minor and managed conservatively. There was no mortality. Median length of stay was 2.6 ± 3 days. At one-year follow-up, the mean BMI decreased to 29 kg/m2 (±3). In the revisional surgery group, percent excess weight loss reached 75.4% at one year.ConclusionTelemedicine in bariatric surgery is safe, effective, and significantly reduces environmental impact. Remote consultations did not alter clinical decisions or outcomes. Wider adoption could benefit from dedicated digital tools to enhance patient care and sustainability.